ANALYSIS OF UKRAINE’S DEBT SECURITY: PROSPECTS AND CHALLENGES - Vinnytska, Oksana; Korniienko, Tatiana (SWorld-Ger Conference proceedings, 2024)
It is substantiated that the conditions of military conflict emphasise the importance of security issues in all spheres of the State’s life. The country, in the face of a budget deficit, is forced to seek assistance from Western partners and internationa